2021
DOI: 10.18388/abp.2020_5807
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, pattern recognition receptors and autophagy under physiological and pathological conditions, including viral infections

Abstract: Research on the health of mammals invariably shows how dynamic immunology is and how the role of many elements and immune processes of the macroorganism, developed in the process of evolution in protecting against threats, including infections, is changing. Among these elements conditioning the homeostasis of the macroorganism are mitochondria, PRR receptors (pattern recognition receptors) and the phenomenon of autophagy. In the context of physiological and pathological states in the body, mitochondria perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
(178 reference statements)
0
2
0
Order By: Relevance
“…We identified and screened four mitochondrial hub genes ( AMPK , PGC1-α , SLC25A25 , and ARMCX1 ). Recent studies have found that inflammation is usually activated by PRRs on both immune and non-immune cells [ 24 ]. Notably, nucleic acids, proteins, and small metabolites do not normally drive the PRR signalling pathway, because they do not go to the PRRs’ subcellular compartments [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified and screened four mitochondrial hub genes ( AMPK , PGC1-α , SLC25A25 , and ARMCX1 ). Recent studies have found that inflammation is usually activated by PRRs on both immune and non-immune cells [ 24 ]. Notably, nucleic acids, proteins, and small metabolites do not normally drive the PRR signalling pathway, because they do not go to the PRRs’ subcellular compartments [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a wide range of strategies have been developed to induce mitochondrial apoptosis in cancer cells. 12 , 13 Mitochondrial dysfunction can lead to cell death due to ATP deficiency, prompting the proposal of various strategies for stimulating mitochondrial apoptosis in cancer therapy. The antitumor effects of Ca 2+ have led to increased attention on mitochondrial Ca 2+ overload as a promising pathway for inducing mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%